Sosialisasi Akad-akad Ekonomi Syariah pada BUMDes di Desa Kaotan Blimbingsari Banyuwangi - Abd. Rohman Fahruddin; Deni Arifianto (Indonesian Journal Publisher, 2021)
BUMDes is an instrument that drives the macro economy at the village level based on local potential and wisdom. Management of BUMDes in a professional manner can be a solution in order to advance and prosper all elements of village society.BUMDes Mitra Sejahtera is the BUMDes of Kaotan Blimbingsari village which has business activities in the form of buying and selling food and renting agricultural equipment. The management of Mitra Sejahtera BUMDes has been carried out on a traditional conventional basis. The majority of the people in Kaotan Blimbingsarivillage are Muslims with the value of mutual cooperation that thrives in the community.BUMDES business activities must be based on benefits and do not contain elements of persecution (tyranny) for the community.Departing from the spirit of doing changes for the better, the condition of the Kaotan village community and the principles of BUMDes business activities, the authors conclude that the implementation of the Sharia economic system is a solution for BUMDes Mitra Sejahtera. Therefore, the socialization of Islamic economic contracts is an important necessity for the managers of BUMDes Mitra Sejahtera. The socialization material includes Sharia business principles and forms of Sharia contracts.The implementation of this activity is packaged in a workshop. Activities carried out using the method of lectures, discussions and practices at the Kaotan Village-Owned Enterprise. This activity is carried out not once but through several stages in accordance with the material that has been compiled by the presenter